ANALYSIS OF THE INFLUENCE OF THEORY X, Y AND ABRAHAM MASLOW'S THEORY IN SUPPORTING EMPLOYEE PERFORMANCE IMPROVEMENT AT PT FIF BINJAI - Ayu Juni Sihombing; Suwarno; Sherlyna Puasari; Maya Sari; Diwa Ardhaza (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
This research aims to test and know clearly how the effect of X and Y Theory and Abraham Maslow on performance employee of PT FIF Finance Cabang Binjai. This research used quantitative methods that involved 78 respondents. The data was collected using questionnaires division. Data were analyzed using a statistical formula, namely by using multiple regression analysis of the processing performed by SPSS Version 16. Results of regression analysis is Y = 4.478 + 0.448 X1 + 0.317X2 + e. The result of quantitative analysis showed X dan Y Theory and Abraham Maslow Teory have positive influence on productivity employee of PT FIF Finance Cabang Binjai.